REVIEW: EPIDEMIOLOGI, PENANGGULANGAN DAN PEMBERANTASAN PENYAKIT MULUT DAN KUKU (Pembelajaran dari Wabah PMK Indonesia 1887-1997) - Petrus Malo Bulu (Partner, 2023)
Foot and mouth disease (FMD) is one of the most economically important livestock viral diseases in the world. The disease is transmitted either directly or indirectly through contact with a contaminated environment. FMD is characterized by fever and vesicles in the mouth, nipples and feet of the animal. Some of the problems and challenges of FMD can include: economic losses, quarantine restrictions, an increase in the price of meat and other livestock products due to a decrease in supply, which can have an impact on inflation and people's purchasing power, transmission to other animals, decreased livestock production, disease control costs, such as vaccination costs and costs for treating infected animals. Prevention and eradication of FMD requires a comprehensive approach that includes strict adherence to biosecurity measures, vaccination, active surveillance, quarantine, control of animal movement, as well as education and awareness. Key Words: Epidemiology, Prevention and eradication of Food and Mouth Disease, District of Kupang.